AB0232 Predictive Factors for Foot Disability in Rheumatoid Arthritis Patients. (10th June 2014) - Matei, D.; Bighea, A.; Patru, S.; Traistaru, R.
Abstract : Background: More than 90% of people with rheumatoid arthritis (RA) develop symptoms in the foot and ankle over the course of the disease. While each individual deformity is common, it is the combination of deformities that compounds the problem.(1) Objectives: The objective of our study is to evaluate the predictive factors for forefoot impairments in different stages of rheumatoid arthritis (RA) patients. Methods: We followed for 3 years 34 patients with RA. The patients were assessed twice: to the beginning of study and after 1 year. We evaluated the morning stiffness (minutes), the PJN, SJN-number of painful and swollen of the metatarsophalangeal (MTP) joints and, the level of pain (with VAS 100mm), the Health Assessment Questionnaire-walking subscale. The results were analyzed with the statistics programme SPSS. Results: Pain and swelling MTP joint was present in 68% of patients (the average pain on VAS-6.89). The walking disability was present in 47% of patients. We also found an important correlation between the level of pain, swelling and walking disability (HAQ) (R 0.698, R 2 0.551). Conclusions: The significant correlation between the parameters analyzed in our study enables the supporting of the necessity for paying a considerable attention to forefoot assessment in RA patients because of important influence of walking disabilities in active life and participation in work, social and self-care activities. References: http://orthoinfo.aaos.org Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5106